2020
DOI: 10.3390/microorganisms8040478
|View full text |Cite
|
Sign up to set email alerts
|

Heliocephala variabilis and Pseudopenidiella vietnamensis: Two New Hyphomycetous Species in the Microthyriaceae (Dothideomycetes) from Vietnam

Abstract: In a survey of microfungi from plant debris collected in Vietnam, two new hyphomycetous species were found, which belong to the genera Heliocephala and Pseudopenidiella and the family Microthyriaceae (Microthyriales, Dothideomycetes). Maximum Likelihood and Bayesian Inference sequence analyses of the internal transcribed spacers (ITS) and large subunit (LSU) of the ribosomal DNA barcodes allowed assessing the phylogenetic relationships of the new species with other species of the respective genera. Heliocephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The genus is characterised by macronematous, mononematous, erect, straight or flexuous, sometimes sinuate, septate, unbranched or sparingly branched, hyaline, smooth conidiophores. The conidiogenous cells are monoblastic, sometimes sympodially extended, integrated, hyaline that produce a solitary, acrogenous, septate, staurospore composed of a main axis and 3 or more branches verticillate arranged from the basal cell of the main axis (Ingold 1943;Seifert et al 2011). Duarte et al (2015) found that Triscelophorus was polyphyletic, based on ITS analysis, but our phylogenetic analysis, based on two-loci and ITS, showed the genus should be monophyletic.…”
Section: Isthmomyces Oxysporusmentioning
confidence: 67%
See 4 more Smart Citations
“…The genus is characterised by macronematous, mononematous, erect, straight or flexuous, sometimes sinuate, septate, unbranched or sparingly branched, hyaline, smooth conidiophores. The conidiogenous cells are monoblastic, sometimes sympodially extended, integrated, hyaline that produce a solitary, acrogenous, septate, staurospore composed of a main axis and 3 or more branches verticillate arranged from the basal cell of the main axis (Ingold 1943;Seifert et al 2011). Duarte et al (2015) found that Triscelophorus was polyphyletic, based on ITS analysis, but our phylogenetic analysis, based on two-loci and ITS, showed the genus should be monophyletic.…”
Section: Isthmomyces Oxysporusmentioning
confidence: 67%
“…Triscelophorus Ingold was established with T. monosporus Ingold as type species; now, eight species have been accepted in this genus (Ingold 1943;Wijayawardene et al 2017). However, the positions of Triscelophorus in ordinal and familial levels are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations